Kurikulum Merdeka dalam Perspektif Pemikiran Pendidikan Paulo Freire - Madhakomala; Aisyah, Layli; Rizqiqa, Fathiyah Nur Rizqiqa; Putri, Fransiska Desiana; Nulhaq, Sidiq (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
Education itself has the essence of fulfilling the basic needs of human life and becoming a human means to carry out the life of the world in the context of the process of maintaining the necessities of life. Education aims in order to survive as a crystallization of values ​​that are embodied in both the dimensions of psychological, sociological, social and cultural values. Studying an educational science must be related to ontological, epistemological, and axiological. The article aims to present a discussion on the study of educational thinking according to Paulo Freire and its implementation in the independent learning curriculum so that readers can get much more knowledge improvement that can be implemented also in their respective education where independent learning will be intensified by the Minister of Education as a new curriculum that begins practiced in the world of education in Indonesia. The presence of the Independent Learning curriculum, which is currently still in the experimental stage, has similarities with the educational concept proposed by Paulo that education must feel freedom both from freedom of thought and to voice opinions. The independent learning curriculum gives freedom to students in their learning activities, students are free to express their opinions, conduct discussions both with students and with the teacher. This activity is the same as that carried out by Paulo Freire in liberation education, students free themselves to express their opinions